Optimizing Workforce Absorption of Vocational High School Graduates to Prepare for the Era of Industrial Revolution 4.0 - Perdana, Novrian Satria (MIMBAR PENDIDIKAN, 2019)
ABSTRACT: Vocational School is one of the educational unit level institutions, whose role is to create qualified and competent human resources in their fields for the needs of the business and industry. Unfortunately, the needs of the business and industry for a competent workforce still cannot be met, because the quality of the existing Vocational Schools is still lacking. The purpose of this study is to analyze the optimization of the absorption of vocational graduates needed by the business and industry world in an effort to achieve a balance of the labour market in the era of industrial revolution 4.0. This study was using a qualitative approach with secondary and primary data analysis methods. This research was conducted in East Java Province in 2018, by holding discussions with Vocational Schools, Companies, and the East Java Provincial Education Office. The results of this study are required for the integration process of the three educational institutions (vocational, courses, and training), which organize vocational education into three things, namely: sharing resources; integrating the learning process; and equalizing minimum service standards.KEY WORD: Vocational; Labour; Industrial Revolution 4.0.Â ABSTRAKSI: â€œMengoptimalkan Penyerapan Tenaga Kerja Lulusan Sekolah Menengah Kejuruan untuk Mempersiapkan Era Revolusi Industri 4.0â€. Sekolah Kejuruan adalah salah satu lembaga tingkat unit pendidikan yang berperan untuk menciptakan sumber daya manusia yang berkualitas dan kompeten di bidangnya untuk kebutuhan bisnis dan industri. Sayangnya, kebutuhan bisnis dan industri untuk tenaga kerja yang kompeten masih belum dapat dipenuhi, karena kualitas Sekolah Kejuruan yang ada masih kurang. Tujuan penelitian ini adalah untuk menganalisis optimalisasi penyerapan lulusan kejuruan yang dibutuhkan oleh dunia usaha dan industri dalam upaya untuk mencapai keseimbangan pasar tenaga kerja di era revolusi industri 4.0. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis data sekunder dan primer. Penelitian ini dilakukan di Provinsi Jawa Timur pada tahun 2018, dengan mengadakan diskusi dengan Sekolah Kejuruan, Perusahaan, dan Dinas Pendidikan Provinsi Jawa Timur. Hasil penelitian ini diperlukan untuk proses integrasi dari tiga lembaga pendidikan (kejuruan, kursus, dan pelatihan), yang mengatur pendidikan kejuruan menjadi tiga hal, yaitu: berbagi sumber daya; mengintegrasikan proses pembelajaran; dan menyamakan standar layanan minimum.KATA KUNCI: Kejuruan; Tenaga Kerja; Revolusi Industri 4.0.About the Author: Novrian Satria Perdana, M.E. is a Researcher at the Center for Policy Research Education and Culture in the Kemendikbud RI (Ministry of Education and Culture of the Republic of Indonesia), Jalan Jenderal Sudirman, Senayan, Jakarta, Indonesia. E-mail: novrian1711@gmail.comSuggested Citation: Perdana, Novrian Satria. (2019). â€œOptimizing Workforce Absorption of Vocational High School Graduates to Prepare for the Era of Industrial Revolution 4.0â€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 4(2), September, pp.127-142. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (June 1, 2019); Revised (August 17, 2019); and Published (September 30, 2019).